Batu bara : Potensi, Penambangan dan pemanfaatan / Dyah Prabowati; Penyunting, Arum P. Mayasari, Ipung Kandri K. - DYAH PROBOWATI, 1960-; IPUNG KANDRI K.; ARUM P. Mayasari (Citra Aji Parama, 2015)
iv, 60 hlm. : ilus. ; 21 cm.